DNA Damage Response Evaluation Provides Novel Insights for Personalized Immunotherapy in Glioma - Chen, Mu; Huang, Bingsong; Zhu, Lei; Wang, Qi; Pang, Ying; Cheng, Meng; Lian, Hao; Liu, Min; Zhao, Kaijun; Xu, Siyi; Zhang, Jing; Zhong, Chunlong (Frontiers in Immunology, 2022)
Background: DNA damage response (DDR) proficiency is the principal mechanism of temozolomide (TMZ) resistance in glioma. Accumulating evidence has also suggested the determining role of DDR in anticancer immunity. We propose that a comprehensive investigation of the DDR landscape can optimize glioma treatment. Methods: We identified the pronounced enrichment of DDR in TMZ-resistant glioma cells by RNA sequencing. Nine differentially expressed genes between TMZ-sensitive/resistant glioma cells were selected to construct the DDR score through lasso regression analysis. Two glioma cohorts from TCGA and CGGA were interrogated to evaluate the predictive ability of DDR score. Multiple algorithms were applied to estimate the immunotherapeutic responses of two DDR phenotypes. Immunohistochemistry was used to determine the protein levels of PD-L1 and TGFβ in glioma specimens. The oncoPredict package was employed to predict the candidate chemotherapy agents. Results: DDR score exhibited a robust prognostic capability in TCGA and CGGA cohorts and served as an independent predictive biomarker in glioma patients. Functional enrichment analyses revealed that high and low DDR score groups were characterized by distinct immune activity and metabolic processes. Elevated levels of infiltrating immune cells (including CD8+ T cells, CD4+ T cells, and dendritic cells) were observed in the high DDR score glioma. Further, high DDR scores correlated with increased mutation burden, up-regulated immune checkpoints, and tumor immunity activation, indicating a profound interplay between DDR score and glioma immunogenicity. In addition, PD-L1 and TGFβ were overexpressed in recurrent glioma specimens compared with primary ones. Finally, we estimated that PI3K inhibitors may serve as latent regimens for high DDR score patients. Conclusion: Our study highlighted the promising prognostic role of DDR score in glioma. Individual assessment of DDR status for patients with glioma may provide new clues for developing immunotherapeutic strategies.